Adequação da biblioteca do Instituto Federal do Amazonas - Campus Zona Leste em tempos de pandemia: o papel do bibliotecário escolar - Azevedo, Sabrina Pinheiro (Brasil, 2022)
In the last two years, the education system has been suffering as a result of the COVID-19 pandemic, the school library was one of the sectors to be affected by this rapid change, therefore, having to adapt in the best way not to completely paralyze its students. services. It is extremely important to analyze that the School Library is the essential factor in the teaching and learning of students. The present work has as general objective to examine the role played by the librarian in the adequacy of the services offered by the Library of the Federal Institute of Amazonas - Campus Zona Leste, during the pandemic resulting from COVID-19, with this four more specific objectives were elaborated with the function of develop the research, namely: identify how the activities that aim to promote reading are developed; verify how actions that encourage school research are carried out; mention how the practices related to cultural actions are developed and describe how the collaborative work between librarian and teacher is established in the school library. The research is characterized as a field study, of a qualitative nature, having as its universe the Library of the Federal Institute of Amazonas and as the subjects or participants of the research, the librarians of this institution. The data collection instrument was elaborated from a script to carry out a semi-structured interview with the librarians, where the process of adapting their services was analyzed during the suspension of classroom activities. From the content analysis obtained by the interview, it was found that the librarians had difficulties in adapting some of the library projects to the remote format, leaving only basic services in functionality. With the results obtained, it is concluded that due to the COVID-19 pandemic, there were difficulties on the part of the institution's library in adapting its services and projects due to the suspension of school activities.